Longitudinal observation of insulin secretory ability before and after the onset of immune checkpoint inhibitor‐induced diabetes mellitus: A report of two cases - Noriko Fujiwara; Mayu Watanabe; Akihiro Katayama; Yohei Noda; Jun Eguchi; Hitomi Kataoka; Shunsuke Kagawa; Jun Wada (Clinical Case Reports, 2021)
Abstract Immune checkpoint inhibitor‐induced diabetes mellitus is a rare immune‐related adverse event. This report illustrates clinical data and insulin secretory ability before and after the onset of immune checkpoint inhibitor‐induced diabetes.